2019
DOI: 10.1186/s12871-019-0720-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of remote ischemic preconditioning with postconditioning on donor hearts in patients undergoing heart transplantation: a single-center, double-blind, randomized controlled trial

Abstract: Background The cardioprotective effect of remote ischemic preconditioning (RIPC) in cardiovascular surgery is controversial. This study investigated whether RIPC combined with remote ischemic postconditioning (RIPostC) reduces myocardial injury to donor hearts in patients undergoing heart transplantation. Methods One hundred and twenty patients scheduled for orthotopic heart transplantation were enrolled and randomly assigned to an RIPC+RIPostC group ( n … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Longer recovery times were noted for those hearts that experienced a preconditioning stimulus longer than 30 minutes, suggesting that ischaemic times longer than this are harmful rather than cardio-protective. A subsequent double-blind randomized controlled trial on the cardioprotective effect of remote IPC on donor hearts in patients undergoing heart transplantation was published in April, 2019 with favourable results [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer recovery times were noted for those hearts that experienced a preconditioning stimulus longer than 30 minutes, suggesting that ischaemic times longer than this are harmful rather than cardio-protective. A subsequent double-blind randomized controlled trial on the cardioprotective effect of remote IPC on donor hearts in patients undergoing heart transplantation was published in April, 2019 with favourable results [8].…”
Section: Discussionmentioning
confidence: 99%
“…The authors cannot in any way be certain of the reasons for the favorable outcome of this heart transplantation following [8] Donor hearts are increasingly being harvested following circulatory deaths in an effort to broaden the donor pool. More focused studies on the effects of ischaemic preconditioning in the course of cardiac transplantations such as the one described here may shed more light on the clinical significance of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous evidence has indicated that, volatile anesthetic agents (isoflurane, sevoflurane and desflurane) have the potential to provide organ(e.g., heart, kidney, brain) protection via pre-and post-conditioning-like mechanisms. 28 Most CPB machines at Fuwai Hospital are equipped with sevoflurane vaporizers, enabling sevoflurane administration during CPB for anesthesia maintenance and the employment of sevoflurane preconditioning (SPreC) and sevoflurane post-conditioning 34 One hundred and twenty patients scheduled for heart transplantation were enrolled and randomly assigned into RIPC+RIPostC group (n=60) or control group (n=60). The findings indicated that, RIPC+RIPostC significantly reduced serum cTnI levels at 6 h after aortic declamping, but there was no significant difference with respect to in-hospital morbidity and mortality between the two groups.…”
Section: Sevoflurane Conditioningmentioning
confidence: 99%
“…The findings indicated that, RIPC+RIPostC significantly reduced serum cTnI levels at 6 h after aortic declamping, but there was no significant difference with respect to in-hospital morbidity and mortality between the two groups. 34 Chinese Medical Sciences Journal…”
Section: Sevoflurane Conditioningmentioning
confidence: 99%
“…An RIPC intervention done to heart transplant recipients together with post conditioning 20 min after aortic declamping reduced cTnI levels at 6 hours after transplantation. 18 In a recent trial RIPC done to living liver donors reduced postoperative aspartate aminotransferase levels in liver recipients, 19 whereas a pilot study of the RIPCOLT trial with RIPC done on liver transplant recipients demonstrated no short-term benefits. 20 Direct ischaemic preconditioning with clamping of liver hilum in DBD was not was not beneficial and could even induce excessive ischaemic damage.…”
mentioning
confidence: 99%